Negotiating cultural and religious identity through prophetic ethos: A critical discourse analysis of Kuntowijoyo’s Impian Amerika - Erik Tauvani Somae (NOTION: Journal of Linguistics, Literature, and Culture, 2026)
In Indonesia, there are literary works deal with the issues of multiculturalism and religion, but those synthetize both in creative way are still rare. This study examines Kuntowijoyo’s novel Impian Amerika as a case of what the author terms “prophetic multicultural literature”, a literary form integrating multicultural values with a prophetic ethos grounded in humanization, liberation, and transcendence. Employing Teun A. van Dijk’s Critical Discourse Analysis (CDA). The study analyzes the novel across three dimensions: textual structure, social cognition, and social context. The findings reveal that: (1) Impian Amerika construct prophetic multiculturalism through the interplay of religious and cultural values rooted in a prophetic ethos; (2) multiculturalism identity in the novel is shapes by minority status, diasporic longing, and Indonesian nationalism; and (3) the novel advanced a moderate religious discourse that transitions from textual normativity to contextual and historical interpretation. Theoretically, this study contributed to the operationalization of prophetic multicultural literature as an analytical category within CDA, offering a frame for examining the intersection of religion, identity, and social justice in literary discourse.